COMPONENTS OF THE PEDAGOGICAL MODEL OF THE DEVELOPMENT OF THE COORDINATING ABILITIES OF STUDENTS AGED 7-10 IN SPECIAL CORRECTIONAL AND GENERAL EDUCATIONAL SCHOOLS - Akhmetov S.M.; Aleksanyants G.D.; Medvedeva O.A.; Volkov A.V.; Selikhova E.G. (Theory and Practice of Physical Culture, 2023)
Objective of the study was to develop a pedagogical model (structural components) of the process of developing the coordination abilities of children aged 7-10 in special correctional and general education schools based on their psychophysiological parameters. Methods and structure of the study. The study was performed at the laboratory of the Department of Anatomy and Sports Medicine of the Kuban State University of Physical Culture, Sports and Tourism, gymnasium No. 18, school No. 63 and a special correctional boarding school in Krasnodar. The survey involved 311 healthy junior schoolchildren aged 7-10 years (boys - 149, girls - 162) and 96 (boys - 49, girls - 47), peers suffering from sensorineural hearing loss (III-IV degree). To achieve the formulated goal, psychophysiological parameters were determined in the observed children. Also used: analysis of scientific literature, pedagogical testing, modeling (logical), design. Students participated on a voluntary basis, informed consent was obtained from parents and representatives of children. Results and conclusions. The proposed pedagogical model for the development of coordination abilities of students in special correctional and general education schools, taking into account psychophysiological indicators, implements the basic target settings, their solution, providing predictable improvements in the physical qualities of children 7-10 years old.